2021
DOI: 10.3390/min11111241
|View full text |Cite
|
Sign up to set email alerts
|

Uranium (VI) Adsorbate Structures on Portlandite [Ca(OH)2] Type Surfaces Determined by Computational Modelling and X-ray Absorption Spectroscopy

Abstract: Portlandite [Ca(OH)2] is a potentially dominant solid phase in the high pH fluids expected within the cementitious engineered barriers of Geological Disposal Facilities (GDF). This study combined X-ray Absorption Spectroscopy with computational modelling in order to provide atomic-scale data which improves our understanding of how a critically important radionuclide (U) will be adsorbed onto this phase under conditions relevant to a GDF environment. Such data are fundamental for predicting radionuclide mass tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…The F-test and dimensional Hamilton test was performed to justify each path included in the fit [33]. Finally, shells were chosen that gave the best fit, e.g., split oxygen shell, and that were chemically reasonable based on the chemistry of each system (see Supplementary Material SS1) [28][29][30][34][35][36][37][38][39].…”
Section: Sr K-edge Gixafs Analysesmentioning
confidence: 99%
“…The F-test and dimensional Hamilton test was performed to justify each path included in the fit [33]. Finally, shells were chosen that gave the best fit, e.g., split oxygen shell, and that were chemically reasonable based on the chemistry of each system (see Supplementary Material SS1) [28][29][30][34][35][36][37][38][39].…”
Section: Sr K-edge Gixafs Analysesmentioning
confidence: 99%
“…The uranium oxides are well studied with the U­(IV) oxidation state favoring UO 2 at lower oxygen pressures trending up in oxidation states as the oxygen pressure increases, resulting in a U 3 O 8 with an average oxidation state (AOS) of 5.33 and eventually in UO 3 with a U­(VI) oxidation state. The oxychloride region is dominated by a UOCl 2 when the oxidation state is U­(IV), and while under a higher oxygen presence, UO 2 Cl 2 with a U­(VI) oxidation state is favored. , Deeper investigation into the U­(VI) oxidation state shows that the number of chlorine atoms bonded seems to be a function of chlorinity of the media and everything from UO 2 Cl to UO 2 Cl 5 can be formed with a similar uranyl base. Many of these are synthesized and studied within aquo-choro or acidic media. In these cases, it was identified that the typical bonds observed by extended X-ray absorption fine structure (EXAFS) measurements are a shortest-bond-length U-O ax axial bond, signature of the UO 2 , a medium-bond-length U-O eq binding H 2 O or OH – equatorially to the uranium, and some varying number of equatorial longer U–Cl bonds. …”
Section: Introductionmentioning
confidence: 99%